2015
DOI: 10.1097/hjh.0000000000000543
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric carotid and cardiac ultrasound compared with clinical risk scores for the prediction of angiographic coronary artery disease

Abstract: In Echo-Lab, Rome, Italy, the integrated cardiovascular ultrasound study is feasible in a high percentage of patients. The combination of three parameters, that is, score of calcium, cIMT, and LAD velocity, has incremental predictive value for obstructive CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 42 publications
1
5
0
1
Order By: Relevance
“…Усовершенствование ультразвукового оборудования за последние 10 лет позволило качественно изменить возможность исследования магистральных коронарных артерий при помощи серийного трансторакального датчика при выполнении рутинной эхокардиографии [3][4][5]. Проводились работы по сопоставлению данных ультразвукового исследования коронарных артерий с результатами коронароангиографии, в которых была доказана значимая корреляция между высокими скоростями коронарного кровотока и наличием значительных стенозов коронарных артерий, выявленных при проведении коронароангиографии [6,13].…”
Section: Discussionunclassified
“…Усовершенствование ультразвукового оборудования за последние 10 лет позволило качественно изменить возможность исследования магистральных коронарных артерий при помощи серийного трансторакального датчика при выполнении рутинной эхокардиографии [3][4][5]. Проводились работы по сопоставлению данных ультразвукового исследования коронарных артерий с результатами коронароангиографии, в которых была доказана значимая корреляция между высокими скоростями коронарного кровотока и наличием значительных стенозов коронарных артерий, выявленных при проведении коронароангиографии [6,13].…”
Section: Discussionunclassified
“…A persistent flow velocity of ≥ 0.70 m/s was defined as the threshold for a significant stenosis, based on previous experience and recent scientific data (9).…”
Section: Methodsmentioning
confidence: 99%
“…However, these studies were performed on cohorts which only included patients scheduled for coronary angiography. One study demonstrated an excellent statistical relationship between coronary flow velocity of 0.7 m/s and the presence of significant lesions of the left anterior descending coronary artery (LAD) (9). However, there is a lack of studies which compare aliased coronary flow velocity at rest with the functional abnormalities of the left ventricle during exercise stress echocardiography.…”
Section: Introductionmentioning
confidence: 99%
“…Other variables, such as the ultrasound cardiac calcium score may help in the prediction of CAD, as calcium in the valves and other cardiac or vascular sites is associated with the presence of CAD. [36][37][38][39][40][41][42] In conclusion, regarding the first 'diagnostic' point, this is a win for CCTA over stress-echocardiography, in particular thanks to better sensitivity both for obstructive and subclinical CAD when CCTA is directly compared with standard stress-echocardiography (based on wall motion behaviour only); when stress-echocardiography is performed with the newest add-ons, such as measurement of CFVR-LAD, contrast perfusion imaging or other variables, its diagnostic sensitivity clearly improves (sometimes at expense of lower specificity), but the overall accuracy never reaches the numbers of CCTA, which implies direct anatomic imaging of coronary arteries. [43][44][45] Clinical case of a patient presenting with suspected coronary artery disease undergoing stressechocardiography first Figure 1 demonstrates normal wall motion behaviour at rest and Fig.…”
Section: Diagnosing Coronary Artery Diseasementioning
confidence: 99%